How Networks Really Work - White, Russ (Addison-Wesley Professional, 2021)
7+ Hours of Video Instruction There are many elements to a networking system, including hosts, virtual hosts, routers, virtual routers, routing protocols, discovery protocols, etc. Each protocol and device (whether virtual or physical) is generally studied as an individual "thing." It is not common to consider all these parts as components of a system that works together to carry traffic through a network. To show how all these components work together to form a complete system, this video course presents a series of walk throughs showing the processing involved in various kinds of network events, and how control planes use those events to build the information needed to carry traffic through a network. One of the foremost internetworking experts, Russ White leverages his decades of experience in building and troubleshooting large scale networks at the likes of Cisco, LinkedIn, and Juniper to present you with a proven methodology that will help you understand why and how networking technologies work. You will learn to consider the specific problems being solved, why specific solutions are chosen, and how solutions relate to one another. In addition to providing a solid overview of many common protocols and solutions, this valuable insight helps you develop the ability to understand why you should make particular implementation decisions and what the tradeoffs are in each situation, enhance your troubleshooting skills by understanding how each technology works and what problems might arise with any solution, and finally to quickly understand new technologies as they are released by relating them to previously developed technologies. The course begins with the discovery of the information a host needs to send traffic and the forwarding process within a network device. The first walk through is simple, but they will build in complexity until traffic carried in an overlay through a hardware optimized forwarding plane is explained. Along the way, the four problems a control plane must solve will be exposed along with the solutions commonly used to solve these problems. After this basic information is covered, more advanced situations will be considered, including network resilience from a control plane perspective and fast reroute techniques. About the Instructor Russ White began working with computers in the mid-1980s, and computer networks in 1990. He has experience in designing, deploying, breaking, and troubleshooting large scale networks ...